2012
DOI: 10.1124/jpet.111.187732
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinetics of Indoxyl Sulfate in Humans and Its Renal Interaction with Angiotensin-Converting Enzyme Inhibitor Quinapril in Rats

Abstract: Indoxyl sulfate (IS) is an organic anion uremic toxin that accumulates in patients with chronic kidney disease (CKD). The aims of this study were to examine the kinetic profiles of IS in humans at a steady state after multiple doses of L-Trp, a precursor of IS, and the in vivo interaction of IS with the angiotensin-converting enzyme inhibitor quinapril, whose active metabolite is a substrate of organic anion transporter 3 (OAT3) in rats. First, 12-h kinetics after single doses of Trp (2, 4, and 8 g) were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These include renal tubular secretion (IS, HA) [52] , metabolic factors (ADMA) [53] , intestinal secretion, absorption and generation (UA) [54] , (indoles, phenols) [29] , [55] , [56] , (IS) [57] , [58] . [26] , [59] , [60] . Impressive differences in serum concentration of different solutes, either adjusted or not for Kt/V urea , were found in our present study (ranging from 72 to close to 100%), confirming previous data in another hemodialyzed population (concentration differences ranging from 66 to 100%) [26] , so that the same interfering factors may also play an as important role in dialysis patients as in non-dialyzed CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These include renal tubular secretion (IS, HA) [52] , metabolic factors (ADMA) [53] , intestinal secretion, absorption and generation (UA) [54] , (indoles, phenols) [29] , [55] , [56] , (IS) [57] , [58] . [26] , [59] , [60] . Impressive differences in serum concentration of different solutes, either adjusted or not for Kt/V urea , were found in our present study (ranging from 72 to close to 100%), confirming previous data in another hemodialyzed population (concentration differences ranging from 66 to 100%) [26] , so that the same interfering factors may also play an as important role in dialysis patients as in non-dialyzed CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial toxins might act as competitive inhibitors of OAT tubular secretion of both endogenous solutes and drugs, and vice versa, thereby increasing systemic exposure. For example, OAT1 and OAT3 mediated tubular secretion of indoxyl sulfate is competitively inhibited by non-steroidal anti-inflammatory drugs (NSAIDs), quinapril and probenecid [76,77], which may increase systemic exposure of drugs and/or indoxyl sulfate. Indoxyl sulfate, CMPF and hippuric acid also have inhibitory effects on OAT1 and OAT3 activity [7880].…”
Section: Effects Of Microbial Toxins On Drug Transportersmentioning
confidence: 99%
“…Indoxyl sulfate is a well‐known uremic toxin that interacts with organic anion transporters. Transport by SLC22A6, SLC22A8 and SLCO1B3 was determined using RP‐HPLC–UV (Enomoto et al, ), RP‐HPLC–FL (Fujita et al, ) and LC/ESI–MS/MS (Sato et al, ), respectively. From these studies, it is suggested that indoxyl sulfate is a substrate for not only renal transporters SLC22A6 and SLC22A8 but also hepatic transporter SLCO1B3.…”
Section: Transport Of Endogenous Compounds As Determined By Chromatogmentioning
confidence: 99%